Approaching the ‘Trauma Aesthetic’ in Kazuo Ishiguro’s Novels: The Grey Zone and the Manipulation of Memory - Rusu, Iris (East-West cultural passage, 2025)
This article discusses the grey zone and the manipulation of memory evinced by the narrators of Kazuo Ishiguro’s novels, with special emphasis on (1982), (1986), (1989), and (2005). It will show how the unreliable Ishigurian narrators allow for the use of a trauma methodology that focuses on what Primo Levi called ‘the grey zone.’ In recent trauma research, the contentious issue of ‘perpetrator trauma’ has started to gain scholars’ interest: Michael Rothberg’s ‘implicated subject,’ for instance, or Dominick LaCapra’s notion of ‘empathic unsettlement’ go beyond the traditional trauma model and challenge the fixed dichotomic relationship between perpetrators and victims. This view does by no means deny the trauma of the victims but rather indicates that, in Ishiguro’s novels, perpetrators are rarely purely evil and can even suffer from PITS (Perpetration-Induced Traumatic Stress). Rather than making excuses for unspeakable acts, my approach aims to explore the relationship between guilt, shame, and what psychologists call moral injury, in relation to Ishigurian narrators. This article will show that in the aforementioned novels, the main characters, as well as secondary and episodic ones, are, at times, both perpetrators and victims.